Association between Circulating Fibrinogen Level and Severity of Coronary Artery Disease in Type 2 Diabetic Patients with Chronic Stable Angina (Bangladesh Heart Journal, 2021)
Background: Prevalence of coronary artery disease (CAD) among Bangladeshi population is higher in urban than rural population. Among the conventional risk factors diabetes mellitus is a major concern for Bangladeshi population. Fibrinogen (Fg) in plasma is associated with severity of CAD in some populations with acute coronary syndrome.Objective: The aim of the study was to find out the correlation between circulating fibrinogen level and severity of coronary artery disease in patients with type 2 diabetes mellitus with chronic stable angina (CSA).Methods: The study was carried out in the Department of Cardiology, National Institute of Cardiovascular Diseases (NICVD), Dhaka from October 2015 to March 2016.Total 132 patients with chronic stable angina (CSA) and type 2 diabetes mellitus who got admitted for coronary angiogram were included in the study and they were divided into 2 groups according to the on admission level of fibrinogen. Coronary angiogram (CAG) was performed in all patients. The severity of the CAD was assessed by angiographic vessel score and Gensini score.Results: Mean Gensini score was 27.0±22.3 vs 22.2±16.4 and mean vessel score 1.6±0.9 vs 1.2±1.0 in group I and group II respectively (p=0.03 and 0.04, respectively). There was positive correlation between Fg and CAD severity in term of vessel score (r=0.19) and Gensini score (r=0.15). Univariate and multivariate analysis revealed that dyslipidemia, smoking and elevated fibrinogen were the independently significant predictors of severe CAD in type 2 diabetic patients with CSA.Conclusion: Elevated plasma fibrinogen positively correlates with the severity of CAD in patients with diabetes mellitus having chronic stable angina.Bangladesh Heart Journal 2020; 35(2) : 106-113